Forecasting Entertainment Tax Revenue Targets Using Regression and Time-Series Analysis: A Case Study in Sumedang Regency - Tresnajaya, Rd. Tatan Jaka; Supriyadi; Sabnita, Nina (Indonesian Scientific Publication, 2025)
Local governments in Indonesia are granted fiscal autonomy to manage and optimize regional income sources, including local taxes, as a form of Local Own-Source Revenue (PAD). One such tax is the entertainment tax, which plays a significant role in supporting regional development. This study focuses on identifying key factors that influence entertainment tax revenue in Sumedang Regency, West Java and aims to construct a reliable model for projecting future revenue. Employing a mixed methods approach, the research integrates qualitative analysis—conducted through literature review and document analysis—with quantitative techniques, including multiple linear regression and time-series forecasting. This combination allows for a comprehensive understanding of the determinants of entertainment tax performance and provides a data-driven foundation for more accurate and sustainable fiscal planning at the regional level. The findings indicate that entertainment tax revenue is influenced by the number of entertainment venues, population size, tourist visits, GRDP in the tourism sector, GRDP at current prices (ADHB), BI rate, national inflation rate, and per capita income.